FAKTOR–FAKTOR MALADMINISTRASI DALAM PENGELOLAAN DANA DESA DI DESA UBUNG KECAMATAN JONGGAT KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Udaya Madjid; Karina Dewi Saefitriana (Jurnal Media Birokrasi, 2019)
And Development of Community Empowerment and Village (DPMD) central Lombok conduct and examination administration of Ubung Village and find errors administration that occurs at each fiscal year 2014, 2015 and 2016, it makes the writer wanted to know why the Ubung Village always goes wrong administration of village fund management so that the writer did some research with the title “Factors Maladministration in the Village Fund Management in the Ubung Village Jonggat Central Lombok Regency West Nusa Tenggara Province” This study uses ombudsman theory aout clasification about maladministration. And this study uses qualitative methods with an inductive aproach. In this study,the writer uses the methodof collecting data through interviews, observation and documentation. As for the data analysis technique usesd is the reduction of the data, the presentation of the data and the conclusion. The result of this research explains that there are several factors the occurrence of maladministration in the Ubung Village among other delays go on, incompetence, abuse of authority, negligece law and leadership intervention. As for the efforts made by DMPD and Inspetorat namely training, coaching/mentoring, socializing and technical guidance. Whereas the sanction provied that recomendation repair, reprimand and detention of funds. Keyword : the village fund, Maladministration